A mixture detection method based on separate amplification using primer specific alleles of INDELs-a study based on two person's DNA mixture. (February 2017) - Liu, Jinding; Wang, Jiaqi; Zhang, Xiaojia; Li, Zeqin; Yun, Keming; Liu, Zhizhen; Zhang, Gengqian
Abstract: Samples containing unbalanced DNA mixtures from individuals often occur in forensic DNA examination and clinical detection. Because of the PCR amplification bias, the minor contributor DNA is often masked by the major contributor DNA when using traditional STR or SNP typing techniques. Here we propose a method based in allele-specific Insertion/Deletion (INDEL) genotyping to detect DNA mixtures in forensic samples. Fourteen INDELs were surveyed in the Chinese Han population of Shanxi Province. The INDELs were amplified using two separate primer-specific reactions by real-time PCR. The difference Ct value of the 2 reactions (D-value) were used for determination of the single source DNA. INDELs types and further confirmed by electrophoresis separation. The minor allele frequency (MAF) was above 0.2 in 10 INDELs. The detection limit was 0.3125 ng–1.25 ng template DNA for real-time PCR in all 14 INDEL markers. For single source 10 ng DNA, the average D-value was 0.31 ± 0.14 for LS type, 6.96 ± 1.05 for LL type and 7.20 ± 1.09 for SS type. For the series of simulated DNA mixture, the Ct value varied between the ranges of single source DNA, depending on their INDEL typing and mixture ratios. This method can detect the specific allele of the minor DNA contributor as little as 1:50 in rs397782455 and rs397696936; 1:100 in rs397832665, rs397822382 and rs397897230; the detection limit of the minor DNA contributor was as little as 1:500–1:1000 in the rest INDEL markers, a much higher sensitivity compared with traditional STR typing. The D-value variation depended on the alternation of dilution ratio and INDEL types. When the dilution was 1:1000, the maximum and minimum D-values were 8.84 ± 0.11 in rs397897230 and 4.27 ± 0.19 in rs397897239 for LL and SS type mixture, the maximum and minimum D-values were 9.32 ± 0.54 in rs397897230 and 4.38 ± 0.26 in rs 397897239 for LL(SS) and LS type mixture, separately. Any D-value between 0.86 and 5.11 in the 14 INDELs indicated the presence of mixture. The separate amplification strategy based on real-time PCR provides a promising and convenient method for detection of unbalanced DNA mixture for Chinese Han population. Highlights: QPCR detection method was established based on primer-specific amplification of INDEL. The difference of Ct value of L- and S-reaction (D-value) was used to typing DNA. The system can detect minor DNA in 1:500 to 1:1000 mixture in 9 INDELs. The polymorphism of 14 INDELs in Chinese Han population from Shanxi was investigated. This method is an effective tool to exclude non-related suspects.